Stability of Networked Control System (NCS) with discrete time-driven PID controllers. (September 2015) - Dasgupta, Soumya; Halder, Kaushik; Banerjee, Shohan; Gupta, Amitava
Abstract: This paper presents a practical methodology to analyze the stability of a control loop consisting of a continuous time plant and a discrete PID controller connected as a NCS. With this methodology, it is possible to extend useful modern techniques like lifting systems developed for memory-less controllers to cover practical control loops. The methodology is demonstrated with a real-time simulation of a representative system, using a NCS test bench. Highlights: NCS has been represented in this paper as a switched system model. PID controller design using the concepts of lifting. LMI based methodology to design controller with memory to control a plant over a network with jitter and/or data-loss has been proposed. The methodology has been demonstrated with credible online simulation and has been compared with offline results.